İŞ SAĞLIĞI VE GÜVENLİĞİ KANUNU'NA GÖRE İŞVERENİN GENEL YÜKÜMLÜLÜKLERİ - (:unkn) unknown (My University, 2014)
6331 sayılı İş Sağlığı ve Güvenliği Kanunu ile ilk defa sadece iş sağlığı ve güvenliği alanına ilişkin hükümleri içeren bir Kanun yürürlüğe girerek tüm çalışanlar kapsam içine alınmıştır. Kanunun geneli işverenin yükümlülüklerinden oluşmakta ve birçok husus da çıkarılmış ya da çıkarılacak Yönetmeliklere bırakılmaktadır. Buna göre işveren, çalışanların işle ilgili sağlık ve güvenliğini sağlamakla yükümlü olup bu çerçevede, her türlü tedbirin alınması, organizasyonun yapılması, gerekli araç ve gereçlerin sağlanması, sağlık ve güvenlik tedbirlerinin değişen şartlara uygun hale getirilmesi ve mevcut durumun iyileştirilmesi için çalışmalar yapacaktır. İşverenin risk değerlendirmesi yapması veya yaptırması yükümlülüğü de Kanunun önleme siyasetine ağırlık verdiğini göstermektedir. Çalışmamızda, işverenin iş sağlığı ve güvenliği alanındaki yükümlülükleri ilgili mevzuat uyarınca incelenmiş, her şeyden önce iş sağlığı ve güvenliği bilincini oluşturmanın ve eğitimin önemi vurgulanmıştır.

With the law no 6331 Occupational Health and Safety Law, first time a law inured only about occupational health and safety field which includes all the workers. As a whole the law formed, responsibility of the employer. The other subjects depend on the regulations which were issued or will be issued. The employer shall have a duty to ensure the safety and health of workers in every aspect related to the work. In this respect, the employer shall; take the measures necessary for the safety and health protection of workers, including prevention of occupational risks and provision of information and training, as well as provision of the necessary organization and means and shall ensure that these measures are adjusted taking account of changing circumstances and aim to improve existing situations. The employer carries out a risk assessment or gets one carried out and this shows the Law focuses on proactive approach. At this research, within the scope of legislation, the employers obligations in the field of safety and health were analysed, primarily the importance of creating occupa- tional health and safety awareness and its training were emphasised.
According to Occupational Health and Safety Law General Responsibility of the Employer
Keywords: Hukuk